Study on three-part pricing method of pumped storage power station in China considering peak load regulation auxiliary service. Issue 1 (February 2021) - Song, Xinfu; Zhai, Xujing; Chen, Weiwei; Xue, Jingjie; Wang, Pengchao
Abstract: The existing operation mode of pumped storage power station in China has the problems of low profit and unable to fully reflect the value of various auxiliary services. In this regard, this paper puts forward a more reasonable and more suitable price mechanism of pumped storage power station in China. Firstly, this paper studies the pricing method considering dynamic depreciation. Then, on the basis of the feed-in tariff of thermal power units, the avoidable cost method is used to study the pricing method of grid price for pumped storage power station. Finally, based on the efficiency loss cost, generation opportunity loss cost and unit start-up and shut-down cost of pumped storage power station participating in peak load regulation auxiliary service market, a three-part electricity price mechanism is proposed. The electricity price mechanism proposed in this paper is helpful to correctly evaluate the benefit of pumped storage power station and promote the construction and development of pumped storage power station.